Machfud Arifin-Mujiaman Couple Campaign Strategy in the 2020 Surabaya Mayor Election - Jason Joshua Chandra; Yohanes Nainggolan (Catalist Indo Publisher, 2026)
Background This study aims to determine the campaign strategy of the Machfud Arifin-Mujiaman pair in the 2020 Surabaya Mayoral Election. The campaign strategy is a system developed by the campaign team that is used in the battle for voters' votes, in its implementation political marketing is used. Political marketing itself has a meaning as a marketing management theory that is applied in the political arena, political marketing is not a concept that sells political parties or candidates to the public. But political marketing is a concept to solve actual problems with programs and issues that are being developed. In political marketing theory, there are four stages that must be carried out by political actors, these stages are known as the 4Ps, namely product, promotion, price (price), and place (place). Methods The research method used in this study is descriptive qualitative, while the data collection techniques used are observation, interviews and documentation. Results The results of this study indicate that there was a big job done by the Machfud Arifin-Mujiaman pair before developing a campaign strategy, through the success team the Machfud Arifin-Mujiaman pair first conducted voter segmentation. After conducting voter segmentation, the Machfud Arifin-Mujiaman pair determined the products to be promoted, there were three products sold by the Machfud Arifin- Mujiaman pair, namely political parties, track records and characteristics of candidates, while promotion was carried out through social media and conventional campaigns , for the selling price or value, Mr. Machfud Arifin in particular as a candidate for Mayor is seen as a figure who is firm, authoritative and charismatic, but the negative impact is that because of his police background Mr. Machfud Arifin can get a negative image in society, for his own place can be seen in various platform and to increase the selling price, the Machfud Arifin-Mujiaman pair invited several influencers such as Atta Halilintar, Sara Fajira and others. There are two campaign strategies used, namely ground attack and air attack. Conclusions There were at least four activities carried out in the ground attack, including party consolidation, the second was forming a winning command post, the third was forming a team of volunteers, and the fourth was blusukan. While the airstrikes were carried out through social media such as Instagram, Facebook, TikTok, and YouTube.